Bioelectrochemical Treatment Technology—The New Practical Approach for Wastewater Management and GHG Emissions Reduction - Babanova, Sofia; Jones, Jason; Wiseman, Kelly; Soles, Jaime; Garcia, Jaime; Huerta, Pedro; Barocio, Daniel; Naito, Ryoji; Arreola, Orlando; Garcia, Gerardo; Bretschger, Orianna (Frontiers in Chemical Engineering, 2022)
This study presents BioElectrochemical Treatment Technology (BETT) as a new wastewater management solution toward the Net-Zero future. The results reported herein were collected from a BETT pilot system installed at a large brewery in Los Angeles, CA, processing 0.6 m3/day of raw brewery wastewater with a high content of fruit pulp. Removal of Chemical Oxygen Demand (COD), Total Suspended Solids (TSS) and protein in mg/L per day or percentage were evaluated over two months of continuous operation of the Demo Unit. The GHG emissions associated with the power consumed, biomass produced, and carbon dioxide emitted were estimated and compared to aerobic and anaerobic solutions. It was demonstrated that BETT can process wastewater with higher organic load than most conventional anaerobic systems. The inflow COD loading varied between 48,550 mg/L to 116,200 mg/L, and BETT achieved up to 33% COD removal in 4-hours HRT. The TSS removal reached values as high as 79% with incoming TSS concentrations up to 34,000 mg/L TSS. BETT did not directly generate methane and demonstrated 89% and 49% lower landfill methane emissions than aerobic and anaerobic technologies, respectively. The overall reduction in CO2 emissions, both direct and indirect, was estimated to be 85-90% compared to existing practices.